GREEN BUSINESS PLAN: TOOL FOR ENTREPRENEURIAL VENTURE IN SUSTAINABLE BUSINESSES - Katerina Hadzi Naumova-Mihajlovska (Institute of Economics-Skopje, 2023)
: Due to climate change, workers, enterprises and economies have been led to focus on sustainable consumption and production. Businesses that are committed to the principles of environmental protection within their activities, while striving to use renewable energy sources and trying to mini mize the negative impact on the environment are defined as green. Main doc ument that explains the business opportunity of green business, identifies the markets to be served and provides information on how it will be carried out is the green business plan. The purpose of the paper is to analyse the envi ronmental aspects that green business plan should have in order to realize a business idea whose basis is environmental protection and on the other hand to emphasize the importance of the same as a necessity for running a successful and sustainable business.
Keywords: green business, environmental challenges, entrepreneurial venture, sustainable business